Diagnosis, clinical symptoms and treatment of Hakim-Adams syndrome - Kozikowska, Marta; Pociecha, Agnieszka; Kmak, Bożena (Quality in Sport, 2024)
Introduction and purpose Normal pressure hydrocephalus (NPH) is a chronic and progressive neurological disorder that affects the accumulation of cerebrospinal fluid (CSF) in the brain's ventricles. The disease is not limited by age, but it is more prevalent in older adults. The accumulation of excess CSF in the brain's ventricles is caused by the obstruction of normal CSF flow, leading to an enlargement of the ventricles and pressure on brain structures. NPH manifests as cognitive disorders, gait disorders, and urinary incontinence. NPH is considered a potentially reversible cause of dementia. This study aims to discuss the etiology, symptoms, differential diagnosis, and treatment methods associated with normotensive hydrocephalus. Materials and methods A comprehensive literature review was conducted through an extensive bibliographic search, with a primary focus on original research articles obtained from reputable databases such as PubMed, BioMed Central, Polish Medical Platform, and Google Scholar. The search was specifically targeted towards articles pertaining to Normal Pressure Hydrocephalus (NPH). Conclusions Normotensive hydrocephalus (NPH) is a complex neurological condition that is characterized by an imbalance between the production and absorption of cerebrospinal fluid (CSF). NPH is classified into idiopathic and secondary types, which helps to determine the possible underlying causes and mechanisms that contribute to the development of the condition. The clinical manifestations of NPH are highly variable, and the diagnostic process can be complicated due to the need to differentiate it from other neurodegenerative disorders. Underdiagnosis or misdiagnosis is common, leading to a decrease in patients' quality of life and, in many cases, disability. The prevalence of NPH is increasing, highlighting the need for further research and the development of novel therapeutic approaches to improve patient outcomes.